2015
DOI: 10.1016/j.bbadis.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 overexpression and irisin ameliorate glucose/lipid metabolic derangements and enhance lipolysis in obesity

Abstract: Irisin is a cleaved and secreted fragment of fibronectin type III domain containing 5 (FNDC5), and contributes to the beneficial effects of exercise on metabolism. Here we report the therapeutical effects of FNDC5/irisin on metabolic derangements and insulin resistance in obesity, and show the lipolysis effect of irisin and its signal molecular mechanism. In obese mice, lentivirus mediated-FNDC5 overexpression enhanced energy expenditure, lipolysis and insulin sensitivity, and reduced hyperlipidemia, hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 38 publications
12
163
0
5
Order By: Relevance
“…Elevated serum irisin concentration has been found to be related to an increase in energy expenditure, weight loss and improved diet-induced insulin resistance in mice [1]. Furthermore, according to experimental data, subcutaneous perfusion of irisin causes a reduction of serum total cholesterol, triglycerides (TG) and free fatty acids (FFAs), as well as hyperglycemia and improved insulin sensitivity in obese mice [6]. However, studies in humans are not consistent and there is still no clear data concerning whether circulating irisin level is associated with improvement of glucose homeostasis and insulin sensitivity [3,[7][8][9].…”
mentioning
confidence: 99%
“…Elevated serum irisin concentration has been found to be related to an increase in energy expenditure, weight loss and improved diet-induced insulin resistance in mice [1]. Furthermore, according to experimental data, subcutaneous perfusion of irisin causes a reduction of serum total cholesterol, triglycerides (TG) and free fatty acids (FFAs), as well as hyperglycemia and improved insulin sensitivity in obese mice [6]. However, studies in humans are not consistent and there is still no clear data concerning whether circulating irisin level is associated with improvement of glucose homeostasis and insulin sensitivity [3,[7][8][9].…”
mentioning
confidence: 99%
“…It has been observed that irisin inhibits hepatic gluconeogenesis and increases glycogen synthesis in type 2 diabetic mice and hepatocytes [11]. We have shown that either FNDC5 overexpression or irisin ameliorates glucose/lipid metabolic derangements and enhances lipolysis in obesity [12]. Moreover, FNDC5 alleviates hepatosteatosis by restoring AMPK/mTOR-mediated autophagy, fatty acid oxidation, and lipogenesis in mice [13].…”
Section: Introductionmentioning
confidence: 82%
“…These data suggested that irisin could function as a protective agent against an excessive influx of energy as it increases energy expenditure. Other authors suggested that the increased irisin levels were secondary to a mechanism similar to the leptin increased levels, i.e., the body increases basal levels of this hormone in response to its resistance (Xiong et al 2015). When Boström et al (2012) published the first results on irisin and carbohydrate metabolism, hormone levels were associated with beneficial effects on health, such as reduced body weight and increased insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that irisin can affect insulin action, suggesting its protective role in the development of obesity and diabetes mellitus (Yang et al 2015). Other studies have shown an inhibitory action of irisin in liver fat accumulation, hypothesizing that irisin supplementation could result in health metabolic effects (Xiong et al 2015, Tang et al 2016). More recently, an agingrelated effect of irisin was demonstrated through its action on mononuclear cell telomere extension (Rana et al 2014) and neurogenesis stimulation (Moon et al 2013), suggesting a preventive role for this hormone in neurodegenerative diseases.…”
Section: Irisinmentioning
confidence: 99%